All Days 2011
DOI: 10.4043/21588-ms
|View full text |Cite
|
Sign up to set email alerts
|

Deployment of Subsea Equipment: Qualification of Large Diameter Fibre Rope for Deepwater Construction Applications

Abstract: This paper describes the SIRIUS (Safe Installation with Ropes In Ultradeep Sea) JIP full scale testing program conducted to determine the bend fatigue performance of large diameter fibre ropes with HMPE fibres (Dyneema®) on small diameter sheaves, together with a summary of the results and the impact the results have on installation operations. The test rig has previously been used for testing of Ø109 mm steel wire ropes and these results will be used as benchmark for the fibre ropes tested at similar Safety F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…It is evident that the internal abrasion is the main contributor to the increase in temperature. Törnqvist et al (2011) support this statement, as they observed that the higher temperatures were between the strands, mainly due to friction from the internal movement.…”
Section: Thermographymentioning
confidence: 65%
See 1 more Smart Citation
“…It is evident that the internal abrasion is the main contributor to the increase in temperature. Törnqvist et al (2011) support this statement, as they observed that the higher temperatures were between the strands, mainly due to friction from the internal movement.…”
Section: Thermographymentioning
confidence: 65%
“…A natural extension from manual visual inspection, is the use of computer vision as a means of continuous condition monitoring for fiber ropes. Törnqvist et al (2011) performed CBOS testing of a large diameter HMPE fiber rope from Dyneema R with experimental results as shown in Figure 9. During the testing, the authors documented the condition of the fiber rope at 25 %, 50 %, 75 % and 100 % of its lifetime.…”
Section: Computer Visionmentioning
confidence: 99%
“…Fatigue investigations on HMPE have been mainly focused on rope bending fatigue performance (e.g. [20]- [24]) as it was identified as the most severe case for handling lines. Nevertheless to be able to quantify the life time expectancy of a rope we have to establish a theory for pure tension fatigue.…”
Section: Synthetic Rope Fatigue Behaviourmentioning
confidence: 99%
“…(Feyrer, 2007, Nabijou andHobbs, 1995;Vennemann et al, 2008), but synthetic fibre ropes are less well-known. There have been some industry studies, the DISH (Deep water Installation of Subsea Hardware) (2001)(2002)(2003)(2004)(2005)(2006) Joint Industry Project involved some testing, and various other offshore projects using synthetic ropes are underway (Tornqvist et al, 2011;Torben et al, 2007;Gilmore et al, 2008;Thomas and Gilmore, 2009), but few results have been published to date. The ropes of interest for these applications, both oceanographic and offshore, are braided.…”
Section: Introductionmentioning
confidence: 97%